PENGADAAN UNIT KESEHATAN KELAS SEBAGAI UPAYA MENDUKUNG PELAYANAN KESEHATAN SEKOLAH DI SD NEGERI 32 AMPENAN - Apriani, Ni Kadek Ratih; Rizka Ayu Aryani; Nunung Pratiwi; Rury Kurniati (Al-mujahidah, 2024)
Procurement of health units in each class as an emergency replacement for the infirmary room which is damaged and requires a long repair period. This service was carried out within 1 week starting on May 13, 2024 to May 18, 2024. The service design carried out is divided into 3 stages, namely; preparation stage, implementation stage and reporting stage. Procurement of class health units is expected to be used by students properly and can replace the function of the infirmary room which is not adequate. With the class health unit, the school and students can collaborate to continue the role and function of the class health unit properly.